2021
DOI: 10.48550/arxiv.2112.12591
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Black-Box Testing of Deep Neural Networks Through Test Case Diversity

Abstract: Deep Neural Networks (DNNs) have been extensively used in many areas including image processing, medical diagnostics, and autonomous driving. However, DNNs can exhibit erroneous behaviours that may lead to critical errors, especially when used in safety-critical systems. Inspired by testing techniques for traditional software systems, researchers have proposed neuron coverage criteria, as an analogy to source code coverage, to guide the testing of DNN models. Despite very active research on DNN coverage, sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(21 citation statements)
references
References 61 publications
(141 reference statements)
0
21
0
Order By: Relevance
“…Similar to code coverage in traditional software systems [14], researchers have proposed several neuron coverage metrics in the context of DNN test selection to prioritize the selection of test inputs with high coverage scores [6][7][8][9][10]. Studies have shown the effectiveness of these approaches for distinguishing adversarial inputs but failed to demonstrate a positive correlation between coverage and DNN mispredictions [15][16][17][18]. Furthermore, for some coverage metrics, reaching maximum coverage can be easily achieved by selecting a few test inputs [15,19], thus putting into question the usefulness of such white-box DNN test selection approaches.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Similar to code coverage in traditional software systems [14], researchers have proposed several neuron coverage metrics in the context of DNN test selection to prioritize the selection of test inputs with high coverage scores [6][7][8][9][10]. Studies have shown the effectiveness of these approaches for distinguishing adversarial inputs but failed to demonstrate a positive correlation between coverage and DNN mispredictions [15][16][17][18]. Furthermore, for some coverage metrics, reaching maximum coverage can be easily achieved by selecting a few test inputs [15,19], thus putting into question the usefulness of such white-box DNN test selection approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the use of white-box DNN test selection approaches is hindered by the requirement for access to the internal structure of the DNN model or the training dataset. This can be a significant limitation, particularly when the model is proprietary or provided by a third party [16].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations